Artificial Intelligence and the Future of Work: A Functional-Identity Perspective. (June 2022) - Selenko, Eva; Bankins, Sarah; Shoss, Mindy; Warburton, Joel; Restubog, Simon Lloyd D.
The impact of the implementation of artificial intelligence (AI) on workers' experiences remains underexamined. Although AI-enhanced processes can benefit workers (e.g., by assisting with exhausting or dangerous tasks), they can also elicit psychological harm (e.g., by causing job loss or degrading work quality). Given AI's uniqueness among other technologies, resulting from its expanding capabilities and capacity for autonomous learning, we propose a functional-identity framework to examine AI's effects on people's work-related self-understandings and the social environment at work. We argue that the conditions for AI to either enhance or threaten workers' sense of identity derived from their work depends on how the technology is functionally deployed (by complementing tasks, replacing tasks, and/or generating new tasks) and how it affects the social fabric of work. Also, how AI is implemented and the broader social-validation context play a role. We conclude by outlining future research directions and potential application of the proposed framework to organizational practice.